Task and Function of Apparatus at Sei Balai Sub-District Office, Batubara Regency, Indonesia - Supiah Ningsih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Coal has good skills and attitudes in work, such as being able to work well with co-workers, so that it can improve its work effectiveness which will provide a great opportunity for employees to move forward and improve their position in the organization. Sei District Head Office District districts. The place of research was carried out at the Sei Sub-District Head Office, Kab. Coal located at Jalan Lintas Sumatra, Durian District, Kab. Coal. Research Time starts from May 2017 to July 2017. The population in this study were all employees at the Sei Sub-District Head Office, Kab. Coal, amounting to 30 people. Employees at Sei Sub-District Head Office District. Coal has good skills and attitudes in work, such as being able to work well with co-workers, so that it can improve its work effectiveness which will provide a great opportunity for employees to move forward and improve their position in the organization. Sei District Head Office District districts.